The Management of Teachers Competency of Islamic Religious Education to Improve Learning Quality in Madrasah Aliyah - Rostini, Deti; Fuadi, Nur; Sutarjo, Moh.; Fajarianto, Otto (International Journal of Psychosocial Rehabilitation, 2020)
Various problems Learning the quality of teacher learning in PAI includes inappropriate management planning between planned and the reality of classroom learning; implementation of learning has not been able to implement various active learning strategies. Head of Madrasah Programs or institutions in improving the quality of teachers of Islamic education, the development of quality learning specifically aims: 1). Teachers are able to study plans to improve professional competence for the development of learning quality 2). Teachers are able to analyze the implementation of competencies in the development of learning quality 3). Learning quality 4). Teachers are able to understand and deal with inhibiting factors in improving teacher professional competencies for the development of learning quality 5). Teachers are able to try to overcome the related factors in improving teacher professional ethics for the development of learning quality 6). Teachers are able to analyze and describe the quality of learning. This type of research is field research (Field Research), where researchers directly obtain data in the field about teacher competency management information for the development of quality learning in Islamic Religious Education. The method of collecting data was through: observation, interviews, documentation and triangulation. The results of data analysis concluded that 1) Planning for the compilation of learning activities comprehensively stipulates the vision, mission, strategy, goals and targets of achievement 2) Implementation through the provision of facilities and assignments to PAI teachers by participating in MGMP teacher workshops, workshops and activities—activities have to do with improving human resources for PAI clump eachers. 3) Scheduled evaluations through classroom supervision activities implemented ideally one semester 2 X but sometimes only 1 time, 4) Inhibiting factors: limited quota of sarpras training participants limited 5) Countermeasures: accessing the internet has to do with academic quality development, active in MGMP. 6) Learning Quality.